Learning Styles of Students in Prva Rije?ka Hrvatska Gimnazija - Jokić, Anita (European Journal of Multidisciplinary Studies, 2018)
Learning is the process of acquiring new or transforming the existing knowledge. Teachers have an important mediatory role in motivating and supporting their students on their path to success and creating friendly working atmosphere. Numerous researchers (Jensen, Dryden, Vos, Willis, Armstrong etc.) recognize that each person prefers different learning styles and techniques and have concluded that most learn using a combination of learning styles. Educators in Croatia have only recently started to recognize these styles and are beginning to shape their teaching techniques and strategies according to their students’ needs and their different or mixed learning styles (visual, aural, verbal, physical, logical, social or solitary). In this paper author describes methods, findings and results of the research conducted on 152 students of Prva rije?ka hrvatska gimnazija (secondary level school). Research was underdone using a structured questionnaire and the results were used to improve and adapt techniques in teaching English as second language. Author has identified preferred learning styles of a specific class (eight classes), groups inside a class and individual students. Also, feedback was given to each student, with advice and suggestions on how to adapt their learning habits to their learning style.